BUSINESS PERFORMANCE MODEL BASED ON PRODUCT DIFFERENCE AND MANAGERIAL ABILITIES IN COFFEE SHOP BUSINESSES - Riyanto, Agus; Hutajulu, Fajar Simon Prederick; Syafei, M. Yani; Sianturi, Gabriel; Fadhilla, Muhammad Azka (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to determine a business performance model that is influenced by product differentiation and managerial capabilities. The research method used was a quantitative approach, from 44 respondents using correlation analysis and coefficient of determination. The results of this research show that the business performance model is strongly influenced by product differentiation and managerial ability.